A escala comum de valores em grupos de aprendizagem de espanhol como língua estrangeira (E/LE) como sistemas adaptativos complexos - Escobar, Patrícia Mussi (2013)
The research was developed based on the thesis of Vetromille-Castro (2007), in which collaboration and autonomy were considered values that fostered interaction and maintained the cohesion and emergency of the group. However, Vetromille-Castro considered that there were other values besides collaboration and autonomy which were shared among co-valorizing individuals (Piaget, 1973). It is precisely on this hypothesis that we developed this work. In this research we studied the interactive process in a group of trainee teachers of Spanish as a Foreign Language (SFL) in virtual learning environment forums. We analyzed the posts of 30 students, the e-learning tutor and two researchers from one of the support centers in four forums of the discipline of Spanish III in a teacher development course in a federal university in southern Brazil in a distance learning modality. The results were obtained by descriptive analysis of a qualitative nature and of a virtual ethnographic interpretation (HINE, 2004). In the interactions we confirmed the hypothesis that there were other values at stake in qualitative changes. In addition to collaboration and autonomy, we identified other values that were common among individuals in the groups, which behaved as complex adaptive (sub)systems (SAC) in each of the four studied forums, also considered as a SAC. Taking into consideration Schwartz s (1992) propositions, we have identified exchanges of mutual benefit (PIAGET, 1973) in each group that was formed in the forums, on a map of values of common scales around values such as equality, friendship, responsibility, creativity, solidarity, among others, besides those already noticed in previous work, namely collaboration and autonomy.